New records of poecilostomatoid copepods (Crustacea) from a coastal system in the Colombian Caribbean with notes on morphology - Juan M. Fuentes-Reinés; Eduardo Suárez-Morales (Check List, 2017)
Seven species of free-living poecilostomatoid copepods are recorded from a coastal system in northern Colombia; one of these records, Oncaea scottodicarloi Heron and Bradford-Grieve, is new for Colombia. The poecilostome copepod fauna from the surveyed area is represented mostly by widespread species commonly found in neritic and oceanic waters of tropical latitudes, but local morphologic data are scarce in the regional literature. Brief diagnostic descriptions of the species recorded for the Colombian copepod fauna are provided together with illustrations of taxonomically important appendages, morphologic remarks, notes on the variability of some species, and their distribution.